A Cross-Sectional Survey of Pain Catastrophising and Acupuncture Use among Breast Cancer Survivors. Issue 1 (February 2017) - Lee, Iris; Garland, Sheila N; DeMichele, Angela; Farrar, John T; Im, Eun-Ok; Mao, Jun J
Introduction: Treatment-related joint pain affects almost half of all women with breast cancer using aromatase inhibitors and is a major reason for terminating treatment. Although acupuncture is becoming an increasingly popular, evidence-based option for treating pain, little is known about the potential influence of psychological factors on acupuncture use. Objective: We aimed to evaluate the association between pain catastrophising and use of acupuncture in breast cancer survivors experiencing arthralgia. Methods: We conducted a cross-sectional survey of arthralgic breast cancer patients. Patients were asked if they had used acupuncture since their cancer diagnosis. The Pain Catastrophising Scale (PCS) was used to measure negative coping styles related to the experience of pain. We performed multiple logistic regression analysis to evaluate the relationship between pain catastrophising and acupuncture use, adjusting for covariates. Results: Of the 424 participants, 69 (16%) reported use of acupuncture since their breast cancer diagnosis. In multivariate analyses, compared to those in the lowest PCS score tertile, patients with the highest PCS scores were more likely to have used acupuncture (p=0.03). In particular, patients with high levels of rumination (p=0.005) and magnification (p=0.008) were more likely to have used acupuncture. Helplessness was not associated with acupuncture use (p=0.23). Conclusions: High levels of pain catastrophising, and specifically the processes of rumination and magnification, were associated with greater acupuncture use. We believe this could have important implications for understanding which population is more likely to seek acupuncture treatment and how this alternative therapy could be better targeted to these patients.